Metformin treatment is associated with improved outcome in patients with diabetes and advanced heart failure (HFrEF) - Benes, Jan; Kotrc, Martin; Kroupova, Katerina; Wohlfahrt, Peter; Kovar, Jan; Franekova, Janka; Hegarova, Marketa; Hoskova, Lenka; Hoskova, Eva; Pelikanova, Terezie; Jarolim, Petr; Kautzner, Josef; et al. (Scientific reports, 2022)
The role of metformin (MET) in the treatment of patients with advanced HFrEF and type 2 diabetes mellitus (DM) is not firmly established. We studied the impact of MET on metabolic profile, quality of life (QoL) and survival in these patients. A total of 847 stable patients with advanced HFrEF (57.4 ± 11.3 years, 67.7% NYHA III/IV, LVEF 23.6 ± 5.8%) underwent clinical and laboratory evaluation and were prospectively followed for a median of 1126 (IQRs 410; 1781) days for occurrence of death, urgent heart transplantation or mechanical circulatory support implantation. A subgroup of 380 patients (44.9%) had DM, 87 of DM patients (22.9%) were treated with MET. Despite worse insulin sensitivity and more severe DM (higher BMI, HbA1c, worse insulin resistance), MET-treated patients exhibited more stable HF marked by lower BNP level (400 vs. 642 ng/l), better LV and RV function, lower mitral and tricuspid regurgitation severity, were using smaller doses of diuretics (all p < 0.05). Further, they had higher eGFR (69.23 vs. 63.34 ml/min/1.73 m2) and better QoL (MLHFQ: 36 vs. 48 points, p = 0.002). Compared to diabetics treated with other glucose-lowering agents, MET-treated patients had better event-free survival even after adjustment for BNP, BMI and eGFR (p = 0.035). Propensity score-matched analysis with 17 covariates yielded 81 pairs of patients and showed a significantly better survival for MET-treated subgroup (p = 0.01). MET treatment in patients with advanced HFrEF and DM is associated with improved outcome by mechanisms beyond the improvement of blood glucose control.
Keywords: Diabetes Mellitus, Type 2; tepový objem; lidé; Treatment Outcome; inzulinová rezistence; metformin; výsledek terapie; Stroke Volume; Heart Failure; Humans; Quality of Life; srdeční selhání; Insulin Resistance; Metformin; diabetes mellitus 2. typu; kvalita života